Ion Specific Effects on the Stability of Halloysite Nanotube Colloids—Inorganic Salts versus Ionic Liquids - Katana, Bojana (J Phys Chem B, 2020)
[Image: see text] Charging and aggregation processes were studied in aqueous dispersions of halloysite nanotubes (HNTs) in the presence of monovalent inorganic electrolytes and ionic liquid (IL) constituents. The same type of co-ion (same sign of charge as HNT) was used in all systems, while the type of counterions (opposite sign of charge as HNT) was systematically varied. The affinity of the inorganic cations to the HNT surface influenced their destabilizing power leading to an increase in the critical coagulation concentration (CCC) of HNT dispersions in the Cs(+) < K(+) < Na(+) order. This trend agrees with the classical Hofmeister series for negatively charged hydrophobic surfaces. For the IL cations, the CCCs increased in the order BMPY(+) < BMPIP(+) < BMPYR(+) < BMIM(+). An unexpectedly strong adsorption of BMPY(+) cations on the HNT surface was observed giving rise to charge neutralization and reversal of the oppositely charged outer surface of HNT. The direct Hofmeister series was extended with these IL cations. The main aggregation mechanism was rationalized within the classical theory developed by Derjaguin, Landau, Verwey, and Overbeek, while ion specific effects resulted in remarkable variation in the CCC values. The results unambiguously proved that the hydration level of the surface and the counterions plays a crucial role in the formation of the ionic composition at the solid–liquid interface and consequently, in the colloidal stability of the HNT particles in both inorganic salt and IL solutions.